2015
DOI: 10.1136/oemed-2014-102629
|View full text |Cite
|
Sign up to set email alerts
|

Temperature as a risk factor for hospitalisations among young children in the Mekong Delta area, Vietnam

Abstract: Temperature was found to be significantly associated with hospital admissions in young children with the highest association between temperature and gastrointestinal infection. The government agencies of Mekong Delta should implement measures to protect children from the changing temperature conditions related to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
2
24
0
2
Order By: Relevance
“…Another study (Xuan et al, 2014a) investigated the association between temperature and mortality in Hanoi, the city in northern Vietnam, but this study did not examine the cause-specific mortality and found a relationship between mortality and cold weather but not with hot weather. Some other published studies (Phung et al, 2015b;Xuan et al, 2014b;Phung et al 2015a) have focused on the relationship between meteorological factors and water-and vector-borne diseases but not non-communicable diseases such as cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Another study (Xuan et al, 2014a) investigated the association between temperature and mortality in Hanoi, the city in northern Vietnam, but this study did not examine the cause-specific mortality and found a relationship between mortality and cold weather but not with hot weather. Some other published studies (Phung et al, 2015b;Xuan et al, 2014b;Phung et al 2015a) have focused on the relationship between meteorological factors and water-and vector-borne diseases but not non-communicable diseases such as cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Significantly associations between ambient temperature and hospital admission for dehydration, intestinal infectious diseases and hands, foot, and mouth among children were also reported in previous studies (84, 85). Although ambient temperature can cause adverse health effects on children, there are few studies about effects of ambient temperature in children's health have been conducted so far, especially in developing countries (91,92).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…To date, few studies have been conducted on the effects of ambient air environment on adverse health effects, particularly on children, in Vietnam. When this research project was started, there was only one study on the relationship between exposure to air pollution and respiratory diseases in children (102) and two studies examining the effects of temperature on children health in Vietnam (92,103). All of those studies were conducted in the South of Vietnam where the climate and air environment are different to the North.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations